Stereocontrolled Synthesis of 1, 4‐Dicarbonyl Compounds by Photochemical Organocatalytic Acyl Radical Addition to Enals. (20th December 2018) - Goti, Giulio; Bieszczad, Bartosz; Vega‐Peñaloza, Alberto; Melchiorre, Paolo
Abstract: We report a visible‐light‐mediated organocatalytic strategy for the enantioselective acyl radical conjugate addition to enals, leading to valuable 1, 4‐dicarbonyl compounds. The process capitalizes upon the excited‐state reactivity of 4‐acyl‐1, 4‐dihydropyridines that, upon visible‐light absorption, can trigger the generation of acyl radicals. By means of a chiral amine catalyst, iminium ion activation of enals ensures a stereoselective radical trap. We also demonstrate how the combination of this acylation process with a second catalyst‐controlled bond‐forming event allows to selectively access the full matrix of all possible stereoisomers of the resulting 2, 3‐substituted 1, 4‐dicarbonyl products.